Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5958/j.0976-058x.48.1.012
|View full text |Cite
|
Sign up to set email alerts
|

Screening of barley germplasm for leaf blight (Bipolaris sorokiniana) resistance

Abstract: Spot blotch or leaf spot, caused by Bipolaris sorokiniana (earlierHelminthosporium sativum) is the most common form of leaf blights of barley which appears in warmer and humid weather. The genetic studies for leaf blight in barley have concluded complex inheritance of leaf blight resistance at adult plant stage. Current Indian barley varieties are mostly susceptible to leaf blight under high input conditions and attempts have been made to introduce resistance for this fungal disease in Indian barley. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
0
0
1
Order By: Relevance
“…Genotypes grouped as resistant had very low level of disease on plants with very small spots which were not spreading further like the susceptible genotypes. Concurrent with the present findings, it has been also reported by Jain et al (2014) who evaluated 85 barley germplasm under epiphytotic conditions and none germplasms were found immune, 68 genotypes were found resistant, 7 were moderately resistant, 7 were moderately susceptible and 3 were found susceptible. Saadi et al (2002) screened barley cultivars and found Beecher, Jimmah 59, Jimmah 54, Omani, K65 and Cooley were resistant against spot blotch.…”
Section: Discussionsupporting
confidence: 91%
“…Genotypes grouped as resistant had very low level of disease on plants with very small spots which were not spreading further like the susceptible genotypes. Concurrent with the present findings, it has been also reported by Jain et al (2014) who evaluated 85 barley germplasm under epiphytotic conditions and none germplasms were found immune, 68 genotypes were found resistant, 7 were moderately resistant, 7 were moderately susceptible and 3 were found susceptible. Saadi et al (2002) screened barley cultivars and found Beecher, Jimmah 59, Jimmah 54, Omani, K65 and Cooley were resistant against spot blotch.…”
Section: Discussionsupporting
confidence: 91%
“…Вредоносный потенциал гриба снижает урожайность зерновых культур (потери урожая зерна составляют от 38 до 87 %) [25]. Ситуация осложняется отсутствием устойчивых к данному заболеванию форм пшеницы и ячменя [26]. Исключение составляют самоклональные линии этих культур, которые способны в условиях относительно жесткого инфекционного фона сохранять урожайность.…”
unclassified